The psychotherapy researcher–practice relationship: Through a clinical supervision lens. Issue 3 (3rd July 2017) - Reese, Robert J.; Gismero González, Elena; Clements-Hickman, Alyssa L.; Clemons, Jade M.; Farook, Minnah W.; Conoley, Collie W.
Abstract : The research and practice gap has long been lamented, but less is known about this divide with regard to clinical training. We surveyed psychotherapy researchers who also engage in clinical supervision, assuming they would be most likely to model research–practice integration in a training context, about how they integrate psychotherapy research and clinical supervision. We found that psychotherapy researcher–clinical supervisors valued psychotherapy research and found it useful for training purposes. Similar to other research, however, respondents indicated that they considered other sources of information, including their own clinical work, more helpful for directing their clinical supervision. Psychotherapy researcher–clinical supervisors also valued psychotherapy process and common factors research more than they did evidence-based and empirically supported treatments. Although the research–practice gap in clinical supervision appears smaller than in a practice context, there was still evidence of a gap. Reasons and implications for these findings are considered.